Colorectal cancer risk and nitrate exposure through drinking water and diet - Espejo‐Herrera, Nadia; Gràcia‐Lavedan, Esther; Boldo, Elena; Aragonés, Nuria; Pérez‐Gómez, Beatriz; Pollán, Marina; Molina, Antonio J.; Fernández, Tania; Martín, Vicente; La Vecchia, Carlo; Bosetti, Cristina; Tavani, Alessandra; et al. (International journal of cancer, 2016)
Ingested nitrate leads to the endogenous synthesis of N‐nitroso compounds (NOCs), animal carcinogens with limited human evidence. We aimed to evaluate the risk of colorectal cancer (CRC) associated with nitrate exposure in drinking water and diet. A case‐control study in Spain and Italy during 2008‐2013 was conducted. Hospital‐based incident cases and population‐based (Spain) or hospital‐based (Italy) controls were interviewed on residential history, water consumption since age 18, and dietary information. Long‐term waterborne ingested nitrate was derived from routine monitoring records, linked to subjects’ residential histories and water consumption habits. Dietary nitrate intake was estimated from food frequency questionnaires and published food composition databases. Odd ratios (OR) were calculated using mixed models with area as random effect, adjusted for CRC risk factors and other covariables. Generalized additive models (GAMs) were used to analyze exposure‐response relationships. Interaction with endogenous nitrosation factors and other covariables was also evaluated. In total 1,869 cases and 3,530 controls were analyzed. Average waterborne ingested nitrate ranged from 3.4 to 19.7 mg/day, among areas. OR (95% CIs) of CRC was 1.49 (1.24, 1.78) for >10 versus ≤5 mg/day, overall. Associations were larger among men versus women, and among subjects with high red meat intake. GAMs showed increasing exposure‐response relationship among men. Animal‐derived dietary nitrate was associated with rectal, but not with colon cancer risk. In conclusion, a positive association between CRC risk and waterborne ingested nitrate is suggested, mainly among subgroups with other risk factors. Heterogeneous effects of nitrate from different sources (water, animal and vegetables) warrant further research. What's new? Nitrate ingested in food and water can react with amines and amides in the gastrointestinal tract, leading to the formation of N‐nitroso compounds (NOCs), which are carcinogenic in animals. In humans, nitrate and several NOCs are probable carcinogens. The aim of the present investigation, a case–control study in Europe, was to examine links between nitrate intake and colorectal cancer (CRC). The findings indicate that CRC risk is increased for waterborne nitrate intake at levels below current international guidelines, particularly in subgroups with other risk factors. Nitrate intake from animal sources was further associated with increased rectal cancer risk.